Study of prestressed concrete beam-column sub-assemblages against progressive collapse - Wu, Wenxuan (Nanyang Technological University, 2022)
This study aims to investigate the parameters that will influence the Progressive Collapse Performance in prestressed concrete beam-column sub-assemblages, specifically the Finite Element Method, which will be utilized to conduct the parametric analysis. It has been proven that prestressed reinforced beams are able to achieve lesser deformations and exhibit better slenderness ratios than normal reinforced concrete beam structures. This has become an increasingly popular method to resist progressive collapse, but only a few studies have examined the progressive collapse performance of prestressed beams as compared to reinforced concrete beams. In this paper, an extensive investigation will be carried out to examine the factors influencing the Progressive Collapse Performance of prestressed beams with different prestressing methods using DIANA FEA. In this paper, post-tensioning concrete beam-column sub-assemblages with bonded and unbonded tendon conditions were simulated by the DIANA FEA, the overall response and failure modes are well predicted by the software, and the parametric studies are performed based on the calibrated models. The results from this study imply that some parameters investigated in this paper did affect the progressive collapse resistance of the structure, such as concrete compressive strength, bottom and top reinforcement ratio, prestressed reinforcement ratio, prestressed reinforcement yield strength, and slenderness ratio. Moreover, each parameter will be evaluated based on its compressive arch action and catenary action capacity. The beneficial effect of catenary action on the progressive collapse resistance of the prestressed structure is quantified by the load and displacement increase factor in this study.